Sustainable Institutional Entrepreneurial Culture and Innovation For Economic Growth - Agnu Dian Wulandari, Oryz; Apriani, Desy; febriansyah, yusuf (Pandawan, 2023)
This article discusses institutional entrepreneurial culture and the enabling factors for sustainable economic growth. This study aims to identify the key factors contributing to institutional entrepreneurial culture development. The research utilizes a qualitative approach, and the results show that an innovative and entrepreneurial culture can enhance a country's long-term economic prosperity. A strong relationship exists between culture, innovation, and long-term economic success. Therefore, it is important to promote an institutional entrepreneurial culture through several factors, such as supporting government policies and programs, developing supporting infrastructure, education, and training, and cooperation between the public and private sectors. This research provides useful insights for policies and interests in the economic sector to promote innovation and entrepreneurship that can enhance economic growth. As such, this article provides important insights for readers interested in developing a sustainable institutional entrepreneurial culture and economic growth.